2020
DOI: 10.1136/bmjgh-2020-004030
|View full text |Cite
|
Sign up to set email alerts
|

Boys are more likely to be undernourished than girls: a systematic review and meta-analysis of sex differences in undernutrition

Abstract: BackgroundExcess male morbidity and mortality is well recognised in neonatal medicine and infant health. In contrast, within global nutrition, it is commonly assumed that girls are more at risk of experiencing undernutrition. We aimed to explore evidence for any male/female differences in child undernutrition using anthropometric case definitions and the reasons for differences observed.MethodsWe searched: Medline, Embase, Global health, Popline and Cochrane databases with no time limits applied. Eligible stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
129
3
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 162 publications
(163 citation statements)
references
References 85 publications
23
129
3
8
Order By: Relevance
“…The difference in severely stunted between males and females could be as a result of morbid state due to poor hygienic practices. Thurstans et al [30] shown that Boys are more likely to be undernourished than girls. These results are similar to those found in Nigeria [31], Northen Uganda [32] and Cameroon [33,34].…”
Section: Fig 1 Frequency Of Exclusive Breast Feedingmentioning
confidence: 99%
“…The difference in severely stunted between males and females could be as a result of morbid state due to poor hygienic practices. Thurstans et al [30] shown that Boys are more likely to be undernourished than girls. These results are similar to those found in Nigeria [31], Northen Uganda [32] and Cameroon [33,34].…”
Section: Fig 1 Frequency Of Exclusive Breast Feedingmentioning
confidence: 99%
“…Finally, we did not stratify our analysis by the infant's sex and as such, we are not able to understand whether our findings differ by sex. Data from children has shown that boys are often more underweight, wasted and stunted whereas there is a sex bias towards girls when identifying malnutrition using MUAC [41,42]. Nonetheless, none of these limitations are likely to invalidate the findings of our study, rather it forms the basis of future work.…”
Section: Implications For Research and Programmingmentioning
confidence: 84%
“…Finally, we did not stratify our analysis by the infant’s sex and, as such, we are not able to understand whether our findings differ by sex. Data from children have shown that boys are often more underweight, wasted, and stunted, whereas there is a sex bias towards girls when identifying malnutrition using MUAC [ 42 , 43 ]. Nonetheless, none of these limitations are likely to invalidate the findings of our study, rather it forms the basis of future work.…”
Section: Discussionmentioning
confidence: 99%